O amanhecer da modernidade em Lúcia Miguel Pereira - Lima, Alana Louise Almeida (2021)
This research aims to analyze how the social process of Brazilian modernity articulates with the literary form of the novel Amanhecer (1938), by Lúcia Miguel Pereira. In this book, a young woman named Aparecida writes her memories from the last two years of her life. Her reflections coexist contradictorily with traditional and modern values, which are revealed over the narrative from the interaction between the narrator protagonist and the other characters in the novel. Having in mind our research objectives, we primarily explored aspects related to the formation of Brazilian literature to understand how our literature formed and organized itself aesthetically face to the historic contradictions that Brazil was submitted. Subsequently, we traced a historical outlook of the social process dramatized in the novel with the purpose of grasping the scenario that engendered the novel of the 1930s and, in addition, we briefly contextualize the female authorship. We used as support theorists and different tendencies in literary studies that expatiate on the relation literature-society, such as Vásquez (1978), Bakhtin (2014), Lúkacs (1978; 2000), Adorno (1970), Candido (1970; 2006), Schwarz (2000; 2002), besides the studies about narrator and characters in the novel genre by Dal Farra (1978), Rosenfeld (1969; 1974), Adorno (1983), Candido (1974). We pursued from this theoretical framework methodological courses and resources that enable us to analyze the process of internalization and formalization of the historical data transformed into structing elements of an artistic form. Finally, we engage to analyze the novel from interpretations under different angles of the narrative, so these interpretations illuminate each other to reveal the articulation between the novel’s literary form and the social process of Brazilian modernization. We evaluate that the book is penetrated by various tensions expressed in ambiguous and contradictory relations between past and present, between female and male characters as well as among white, black and mestizo characters. These tensions are also expressed in our protagonist’s unsteadiness, whose positions do not firm. This is what motivates the writing of her memories: Aparecida’s intention is to fix matters, which seem to be sentenced to be dissolved in new doubts. This confirms Bueno’s (2006) perception that this novel is one of the main representatives of what he named as “novels of the new doubt” from the end of this decade. All these interpretations converge to the comprehension that Amanhecer, even in its purpose of focusing on an intimist look of its narrator and characters, formalizes in its constitutive elements the process of contradictory modernization whereby the country experienced in those times, internalizing social and historical aspects. Such contradiction is founded in a process that do not break up with the traditional structures but reaffirm them with a new appearance. We believe that the results of this research may contribute with new perceptions in studies about the Novel of the 1930’s, especially concerning to the figuration of women – as a narrator and as characters – and of black and mestizo people, aspects that are still insufficiently researched in this period’s narratives.